2019
DOI: 10.2196/13338
|View full text |Cite
|
Sign up to set email alerts
|

Sexting, Web-Based Risks, and Safety in Two Representative National Samples of Young Australians: Prevalence, Perspectives, and Predictors

Abstract: Background The rapid uptake of information and communication technology (ICT) over the past decade—particularly the smartphone—has coincided with large increases in sexting. All previous Australian studies examining the prevalence of sexting activities in young people have relied on convenience or self-selected samples. Concurrently, there have been recent calls to undertake more in-depth research on the relationship between mental health problems, suicidal thoughts and behaviors, and sexting. How … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Focusing on the study design, 2 studies were randomized controlled trials (RCT) [24,25], 12 were open-label single group trials [26][27][28][29][30][31][32][33][34][35][36][37] 2 were randomized studies [38,39], 4 were retrospective cohort studies [40][41][42][43]. The overall sample consisted of 221,419 adolescents.…”
Section: Studies' Selection Characteristics and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the study design, 2 studies were randomized controlled trials (RCT) [24,25], 12 were open-label single group trials [26][27][28][29][30][31][32][33][34][35][36][37] 2 were randomized studies [38,39], 4 were retrospective cohort studies [40][41][42][43]. The overall sample consisted of 221,419 adolescents.…”
Section: Studies' Selection Characteristics and Limitationsmentioning
confidence: 99%
“…An Australian study analyzed the association between sexting and suicidal behaviors, as well as with several other mental health negative outcomes (body image issues, and information and communication technology [ICT] safety risks, including cyberbullying and late-night Internet use). Milton, et al [35] run a survey using computer-assisted telephone interviewing (CATI) and found that sexting (both receiving and sending) were significantly associated with reporting suicidal thoughts and behaviors in the past 12 months. Using an ecological study, Runkle and colleagues [29] analyzed the role of crisis text lines during a weather-related disaster in North and South Carolina, USA (Hurricane Florence).…”
Section: Telepsychiatrymentioning
confidence: 99%
“…Several empirical studies have also found that sexting involvement was associated with participation in undesirable dynamics such as dating violence, sextortion, cyberbullying and grooming [6][7][8][9][10]. Likewise, in some studies, sexting has also been associated with anxiety and depression symptomology, as well as attempted or ideated suicide [11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…Owing to the significant gender differences highlighted in aim 1, 2 logistic regression analyses (separately for men and women) were conducted to address aim 2. Following previously established procedures [ 34 ], 2 logistic regressions were run separately for men and women to identify sociodemographic (including demographics, social connectedness, specific transitional life events experienced in the past 12 months, and whether these life events were perceived as stressful) predictors of STB based on the PSFS.…”
Section: Methodsmentioning
confidence: 99%